Long‐term Intrathecal Baclofen: Outcomes After More than 10 Years of Treatment. Issue 6 (16th December 2013) - Mathur, Sunjay N.; Chu, Samuel K.; McCormick, Zack; Chang Chien, George C.; Marciniak, Christina M.
Abstract : Objective: To report outcomes of intrathecal baclofen (ITB) therapy for spasticity management in a cohort of patients who had received this treatment for at least 10 years. Design: A cross‐sectional survey and retrospective chart review. Setting: An academic rehabilitation outpatient clinic. Participants: Adult patients with spasticity treated with ITB for at least 10 years. Main Outcome Measurements: Surveys included the Brief Pain Inventory, Penn Spasm Frequency Scale, Epworth Sleepiness Scale, Fatigue Severity Scale, Diener Satisfaction with Life, Life Satisfaction Questionnaire, and Intrathecal Baclofen Survey. Results: Twenty‐four subjects completed the surveys. The subjects had been treated with ITB from 10.0‐28.4 years, with a mean (standard deviation) of 14.7 ± 4.2 years. The mean (standard deviation) dose of ITB was 627.9 ± 306.7 μg/d, with only 6 subjects averaging daily dose changes of more than 10% compared with 3 years earlier. The mean (standard deviation) scores on outcomes surveys were the following: 2.6 ± 2.3 for pain severity on the Brief Pain Inventory, 1.4 ± 0.7 for spasm severity on the Penn Spasm Frequency Scale, 7.9 ± 5.4 on the Epworth Sleepiness Scale, 4.1 ± 1.6 on the Fatigue Severity Scale, 19.4 ± 8.1 on the Diener Satisfaction with Life, 3.9 ± 0.9 on the Life Satisfaction Questionnaire, and 8.8 ± 1.9 for overall satisfaction with ITB on the Intrathecal Baclofen Survey. On the Brief Pain Inventory, the mean scores for pain severity and interference of pain with life showed moderate inverse correlations with ITB dose ( r = −0.386, P = .115; and r = −0.447, P = .062, respectively). On the Life Satisfaction Questionnaire, the mean scores for life satisfaction showed statistically significant positive correlation with ITB dose ( r = 0.549, P = .021). Conclusions: The subjects reported low levels of pain, moderate levels of life satisfaction, normal levels of sleepiness, low‐to‐moderate levels of fatigue, infrequent spasms at mild‐to‐moderate severity, and high levels of satisfaction. The efficacy and favorable adverse effect profile of ITB therapy was sustained in this cohort of subjects with more than a decade of treatment.